The validity of the disabilities of the arm, shoulder and hand (DASH) questionnaire in Afrikaans for the Western Cape of South Africa - De Klerk, Susan (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD)--Stellenbosch University, 2022.